Beyond antibiotics: exploring multifaceted approaches to combat bacterial resistance in the modern era: a comprehensive review - Yarahmadi, Aref; Najafiyan, Hamide; Yousefi, Mohammad Hasan; Khosravi, Elham; Shabani, Ehsan; Afkhami, Hamed; Aghaei, Seyed Soheil (Frontiers in Cellular and Infection Microbiology, 2025)
Antibiotics represent one of the most significant medical breakthroughs of the twentieth century, playing a critical role in combating bacterial infections. However, the rapid emergence of antibiotic resistance has become a major global health crisis, significantly complicating treatment protocols. This paper provides a narrative review of the current state of antibiotic resistance, synthesizing findings from primary research and comprehensive review articles to examine the various mechanisms bacteria employ to counteract antibiotics. One of the primary sources of antibiotic resistance is the improper use of antibiotics in the livestock industry. The emergence of drug-resistant microorganisms from human activities and industrial livestock production has presented significant environmental and public health concerns. Today, resistant nosocomial infections occur following long-term hospitalization of patients, causing the death of many people, so there is an urgent need for alternative treatments. In response to this crisis, non-antibiotic therapeutic strategies have been proposed, including bacteriophages, probiotics, postbiotics, synbiotics, fecal microbiota transplantation (FMT), nanoparticles (NPs), antimicrobial peptides (AMPs), antibodies, traditional medicines, and the toxin-antitoxin (TA) system. While these approaches offer innovative solutions for addressing bacterial infections and preserving the efficacy of antimicrobial therapies, challenges such as safety, cost-effectiveness, regulatory hurdles, and large-scale implementation remain. This review examines the potential and limitations of these strategies, offering a balanced perspective on their role in managing bacterial infections and mitigating the broader impact of antibiotic resistance.